The Support Person's Preferences and Perspectives of Physical Activity Programs for Older Adults With Cognitive Impairment - Chong, Terence W. H.; You, Emily; Ellis, Kathryn A.; Cox, Kay L.; Harrington, Karra D.; Rainey-Smith, Stephanie R.; Ames, David; Lautenschlager, Nicola T.; , AIBL Research Group (Frontiers in Public Health, 2021)
Objectives Physical activity (PA) is beneficial for older adults’ cognition. There is limited research investigating perspectives of support persons (SPs) of next-of-kins (NOKs) with cognitive impairment. This exploratory study aimed to investigate perspectives of SPs of older adults with Alzheimer’s Dementia (AD) or Mild Cognitive Impairment (MCI). Methods A telephone survey of 213 SPs of NOKs from the Australian Imaging, Biomarkers and Lifestyle Flagship Study of Ageing (AIBL) was undertaken to quantitatively assess SPs’ beliefs and knowledge about PA benefits, current PA level of their NOK, and PA program preferences. The contribution of age, gender, diagnosis and mental health symptoms was assessed using multiple logistic regression analyses. Results Many SPs were aware of PA benefits for memory (64%) and believed it would help their NOK (72%). Older SP age was associated with less awareness of benefits (p=0.016). SPs caring for male NOKs were more likely to believe that PA would be helpful than those caring for female NOKs (p=0.049). NOK AD diagnosis (rather than MCI) (p=0.014), older age (p=0.005) and female gender (p=0.043) were associated with lower PA levels. SPs were mixed regarding preference for their NOKs to participate in individual (45%) or group (54%) PA. Many SPs wanted to participate in PA with their NOK (63%). Conclusions The results highlight that SPs have high levels of awareness of the cognitive benefits of PA, and describe their preferences regarding PA programs. The findings provide new information to inform targeted public health messaging, PA prescribers and providers, and future research directions.